PERSPEKTIF KUA KECAMATAN BONTOA TERHADAP DAMPAK SOSIAL PERNIKAHAN DI BAWAH UMUR DAN JUDI ONLINE PADA ANAK SEKOLAH - Nur Hilmah Nahar (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2025)
Underage marriage has an impact on children's education, both how they manage their schooling and how they have the opportunity to develop academically. Nonetheless, online gambling has become one of the causes of concentration disorders, decreased learning achievement, and deviant behavior of children at school. To explain this phenomenon in depth, this study used a qualitative approach with a descriptive approach. Data were collected through interviews with community members, educators, community leaders, and people in the KUA of Bontoa sub-district. The results show that this second problem significantly affects children's social and educational development. Marriage and an increase in the number of children cause structural poverty, while online gambling and dependency disrupt the learning process. The KUA of the Bontoa sub-district plays an important role in providing assessment and education to the community. This is done to prevent and assist. This research is expected to help local policies deal with this social problem. The purpose of this article is to investigate the phenomenon of early underage marriage and find causes, and relationships between individuals and society